2018
DOI: 10.17245/jdapm.2018.18.1.27
|View full text |Cite
|
Sign up to set email alerts
|

An epidemiological study on the prevalence of temporomandibular disorder and associated history and problems in Nepalese subjects

Abstract: BackgroundTemporomandibular disorder (TMD) represents a subgroup of painful orofacial disorders involving pain in the temporomandibular joint (TMJ) region, fatigue of the cranio-cervico-facial muscles (especially masticatory muscles), limitation of mandible movement, and the presence of a clicking sound in the TMJ. TMD is associated with multiple factors and systemic diseases. This study aimed to assess the prevalence of TMD in Nepalese subjects for the first time.MethodsA total of 500 medical and dental stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 10 publications
3
25
0
3
Order By: Relevance
“…In this study, the most prevalent degree of TMD severity was the mild TMD for both the females and males in Turkish university students. This agree with the studies which obtained similar findings using the Fonseca questionnaire 13,17,18,21,23,24,[27][28][29] . The prevalence of TMD in females (51,81%) were higher than men (40,34%), although no statistically significant difference were found between TMD severity and gender.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In this study, the most prevalent degree of TMD severity was the mild TMD for both the females and males in Turkish university students. This agree with the studies which obtained similar findings using the Fonseca questionnaire 13,17,18,21,23,24,[27][28][29] . The prevalence of TMD in females (51,81%) were higher than men (40,34%), although no statistically significant difference were found between TMD severity and gender.…”
Section: Discussionsupporting
confidence: 93%
“…In published studies based on FAI, the prevalence rate of TMD was observed to vary from 22,6 to 87% . These prevalence rates were reported by Karthik et al 27 22,6%, Jagdhari et al 22 23%, Rokaya et al 28 30,6%, Conti et al 13 42%, Al Moaleem et al 26 43,5%, Modi et al 21 45,16%, Habib et al 24 46,8%, Bonjardim et al 19 50%, Bicaj et al 29 53,21%, Nomura et al 18 55,4%, relationship between parafunctional habits and TMA are unsolved [46][47][48] . Most studies were observed that the prevalence of bruxism is higher in young adults than in the elderly [49][50][51][52][53] .…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…University of Jaén. Campus de las Lagunillas, 23071, Jaén (Spain) 3 Dental Medical Center Drs. López Collantes.…”
Section: Declarations Ethics Approval and Consent To Participatementioning
confidence: 99%
“…TMDs are the most common orofacial pain condition of non-dental origin. Tenderness and pain of the masticatory muscles, pain in the TMJ, limited jaw joint movements, a clicking or crackling sound on the TMJ grinding and wearing of the teeth, headache, associated dizziness, hearing loss and tinnitus are frequent symptoms [2,3].…”
Section: Introductionmentioning
confidence: 99%